Playing the Past and Alternative Futures: Counterfactual History in Fallout 4 - McCready, Samuel (Loading, 2019)
This article explores representations of history and history for the present in Fallout 4 to illuminate how the gameworld makes clever use of common historical tropes and aesthetics, as well as the genre of the counterfactual in its presentation of a compelling and interactive narrative. Set in the post-apocalyptic landscape of Massachusetts, Fallout 4 employs various sites of historical Massachusetts (Concord, Lexington, Boston) in order to draw the user into the story of the ‘lone survivor,’ the avatar that he or she takes control of. This analysis is interested in the ways that Fallout 4 employs history and the genre of the counterfactual in the production of a compelling narrative that not only invites but impels the player into action to chart a new course for this devastated virtual landscape. The power of counterfactual history lies in its capacity to unravel assumptions about the static nature of historical events, and in its denial of a linear trajectory of history broadly. In the case of Fallout 4, the implementation of a counterfactual story, wherein the nuclear event that shrouded the Cold War period in uncertainty, takes place. It serves as a rejection of the popularly rehearsed narrative of American supremacy triumphing over Communist forces to present the player with a more nuanced interpretation of some of the internal and external tensions that came to define the Cold War period (i.e. cultural malaise, economic instability, the growth of a military-industrial complex). This conflicting presentation of histories both real and imagined provides an opportunity for the player to experience and interact with the game critically as a counterfactual reimagining of the Cold War era. Viewed in this way, the virtual world of Fallout 4 becomes a space where the player can reassess their own understanding of the period, and the nature of historical knowledge production more broadly.